Understanding the Role of Gadoxetic Acid in MRI - Rybczynska, Dorota; Pienkowska, Joanna; Frydrychowski, Andrzej; Szurowska, Edyta; Jankowska, Anna (Current Medical Imaging, 2020)
Background: Radiological imaging methods used at a large scale in the assessment of hepatic lesions include: Ultrasound, computed tomography and magnetic resonance. To further characterize these lesions, specific contrast agents may be added, thus revealing the vascularity of the lesions. Discussion: This review focuses on gadoxetic acid, which is a hepatospecific contrast agent used in MRI. The aim of the review is to briefly explain the mechanism of GA enhancement, describe the enhancement patterns of some benign and malignant hepatic lesions and discuss possible advantages of GA over standard contrast agents. Conclusion: The role of GA in functional MR cholangiography and the idea of accessing liver function by measuring parenchymal enhancement will also be explained.
Keywords: hepatic lesions